EU industrial policy and convergent development in EU peripheries: An assessment of the ‘Important Project of Common European Interest’ (IPCEI) template - Lopes-Valença, H. (JCMS: Journal of Common Market Studies, 2025)
Industrial policy has been enjoying a significant comeback. In the European Union (EU), ‘important projects of common European interest’ (IPCEIs) have become a template for a new, value chain-oriented EU industrial policy. But what does this mean for convergence between ‘peripheral’ and ‘core’ member states? Based on the understanding that convergent development requires opportunities for ‘learning in production’ to accumulate the technological capabilities that are necessary for economic upgrading within value chains, this article advances an in-depth analysis of the implementation of this EU industrial policy template. It argues that IPCEIs have so far offered peripheral countries and their firms few opportunities for learning in production within value chains. In this light, there is a risk that IPCEIs might have limited or even detrimental effects on the prospects for convergence within the EU. The article concludes by considering how this template could be made more conducive to convergent development.